New Approaches to Shifting the Migraine Treatment Paradigm - Johnson, Brian; Freitag, Frederick G. (Frontiers in Pain Research, 2022)
The standard of care paradigm for migraine treatment has been based almost exclusively on approaches that grew out of the happenstance use of market pharmaceuticals. Only methysergide, which has long since been removed from use for safety concerns, the ergotamine family of drugs, and the triptans were explicitly developed with migraine and other vascular headaches in mind. While the forward and innovative thinking to utilize the broad array of agents to treat migraine served millions well, their therapeutic efficacy was often low, and adverse event profiles were troublesome in the least. Advances in biochemical and molecular biology and the application of advanced “designing drugs” methods have brought about a potentially significant shift in treatment. The gepants have efficacies similar to the triptans but without vascular safety or medication overuse concerns. Preventative gepants offer innovative approaches to prevention and efficacy that exceed even the CGRP monoclonal antibodies. Those monoclonal antibodies brought rapid and highly effective outcomes across the spectrum of migraine. They outpaced older oral medication efficacy and eliminated most adverse events while potentially improving compliance with monthly or quarterly dosing. Other serotonin receptors beyond the 5HT1B and1D receptors have been targeted for decades. They now lead us to better formulations of dihydroergotamine for efficacy, convenience, and tolerability, and a 5HT1F-specific acute treatment like the gepants opens new options for acute management. Neuromodulation goes back to the mid-1800's. Our improved understanding of applied biomedical engineering has brought forward several tantalizing devices, including the application of currents distant from the target and patient regulated. Whether these advances change the paradigm of migraine treatment and standards of care remains to be seen, and issues such as cost and patient acceptance will help mold it.